Competency Based Education Training for Sustainable Development: Developing Green Skills for Kenyan Universities a Review - Kirigiah, Richard; Njoka, Moses (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Competency-Based Education and Training (CBET) represents a promising approach to aligning education with industry demands and fostering sustainable development in Kenyan Universities. This review explores the intersection of CBET and sustainable development, focusing on the role of CBET in developing green skills, challenges in implementation, and strategies for integration within higher education institutions. The study employed a qualitative synthesis of existing literature and expert perspectives. The study established that CBET holds potential for nurturing green skills and promoting sustainability, challenges such as inadequate resources, infrastructure, and academia-industry collaboration persist. Addressing these challenges requires a comprehensive approach that prioritizes training, increases awareness, and fosters partnerships between stakeholders. Strategies for integrating green skills into CBET programs include curriculum revision, strengthening academia-industry collaboration, and enhancing education on green technology and sustainable practices. Public investment in sustainable infrastructure and interdisciplinary learning can promote environmental awareness and resilience. By embracing these strategies, Kenyan Universities can prepare graduates to thrive in a rapidly evolving global landscape while contributing to a greener, more equitable economy and society.